Strategies to reduce burn scarring - David G. Greenhalgh (Elsevier, 2024)
Scarring is the primary complication of anyone suffering a burn injury. Despite years of research, there have been few advances in the prevention and treatment of any scar. Recent studies have identified many factors that contribute to scar formation, but despite understanding mechanisms, clinicians are unable to stop the inevitable processes of scarring. The goal of this review is to describe current methods to reduce scarring in burns. At the same time, key questions that should direct future research will be presented. Like many maladies, optimal early care should reduce these complications.